Interatomic Potential of Li-Mn-O and Molecular Dynamics Simulations on Li Diffusion in Spinel Li(1-x)Mn(2)O4 - Lee, Eunkoo; Lee, Kwang-Ryeol; Lee, Byeong-Joo (American Chemical Society, 2017)
An interatomic potential of the Li-Mn-O ternary system has been developed on the basis of the second-nearest-neighbor modified embedded-atom method(2NN MEAM) formalism combined with a charge equilibration (Qeq) concept. The potential reproduces fundamental physical properties (structural, elastic, thermodynamic and migration properties) of various compounds well, including lithium oxides, manganese oxides, and lithium manganese ternary oxides. Through molecular dynamics (MD) simulations using the developed potential, lithium diffusion properties (activation energy for lithium migration and diffusion coefficient) in spinel Li1-xMn2O4 are also reproduced in good agreement with experiments. We have found that the effect of the lithium vacancy concentration is marginal on the activation energy for lithium diffusion in the Li1-xMn2O4 cathode, but it is significant in the lithium diffusion coefficient. The potential can be further utilized for atomistic simulations of various materials phenomena (phase transitions, defect formation, lithiation/delithiation, etc.) in LIB cathode materials.
Keywords: EMBEDDED-ATOM POTENTIALS; REACTIVE FORCE-FIELD; ATOMISTIC SIMULATION; CATHODE MATERIAL; LITHIUM ION; LIMN2O4 SPINEL; REAXFF; LIMNO2; FE; CO